The Relationship between Satisfaction among Residents and the Service Quality in a Mixed-Use Development - Razali, Raudhahtul Fitri; Shamsudin, Zarina; Mat Radzuan, Indera Syahrul; Mohsen, Masfaliza (Research in Management of Technology and Business, 2025)
To meet the city’s expanding population and land scarcity, vertical buildings and mixed-use buildings are being developed, rather than single purpose structures like apartment and commercial building. Despite its complexity, this building poses several challenges to property management. Property management team should aware and understand resident’s requirements and needs to maintain their level of satisfaction and service quality. This study aims to ascertain how well property management company successfully manage the mixed-use development and the level of resident’s satisfaction toward the services provided. This study manage to identify the service quality factors that contribute to the level of resident’s satisfaction. Quantitative method used in this study by distributing 100 questionnaire to the residents in mixed-use development area and qualitative method by handling interview with property manager related to mixed-use development. Correction analysis used in this study to identify the correlation between satisfaction and quality services. The results show that service quality dimensions like assurance and empathy significantly influence the perceived quality of management services in maintenance responses. however, tangible factors and some reliability aspects seem to have less impact.